Analisis Pagelaran Wayang Kulit Ramayana di Desa Sarimulya, Kabupaten Bungo, Provinsi Jambi - Lestari, Putri; Syeilendra, Syeilendra (Jurnal Cerano Seni : Pengkajian dan Penciptaan Seni Pertunjukan, 2026)
Wayang kulit is a traditional performing art. Traditional performances that serve as entertainment, and also serve as a medium for conveying moral values ​​and cultural education. One of the stories often performed in wayang kulit performances is the Ramayana story. A love story of Dewi Sinta and Sri Rama who were separated by King Rahwana. An inspiring story that contains the meaning of true loyalty, therefore I conducted a study aimed at analyzing the performing art of the Ramayana story in wayang kulit performances in Sarimulya Village, Jujuhan Ilir District, Bungo Regency, Jambi Province. This study uses a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation with the main informant, puppeteer Ki Gondo Sumarno who leads the Wiyogo Sari Budaya Karawitan Studio. Data were processed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that wayang kulit performances in Sarimulya Village are still preserved through the activities of the Wiyogo Sari Budaya Studio which was founded in 1988. The puppeteer has an important role in driving the story, conveying character dialogue, and arranging the musical accompaniment of the gamelan. The Ramayana story was chosen because it contains moral values ​​such as loyalty, responsibility, and the triumph of good over evil. Thus, the shadow puppet performance serves not only as entertainment but also as a medium for cultural and moral education for the community.